2004
DOI: 10.1080/08870440412331279764
|View full text |Cite
|
Sign up to set email alerts
|

Illness perceptions and distress in women at increased risk of breast cancer

Abstract: Variation in the levels of distress in women at increased risk of breast cancer has been reported, yet there is limited understanding of the factors that are associated with heightened distress in this population. This study took a theoretical approach using Leventhal's Self Regulatory Model (SRM) to understand variation in distress levels. The study examined the associations between perceptions of breast cancer and distress in women at increased risk of breast cancer, and a comparison sample with no experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 69 publications
2
55
1
10
Order By: Relevance
“…The result for MS and cancer patients in this research also proves that the understanding of illness may change in time. However, from the studies on the revised version of the questionnaire (IPQ-R) we conclude that in terms of illness coherence this stability refers to BC patients (Rees, Fry, Cull, & Sutton, 2004). The inconsistency suggests that one item cannot measure such a complex phenomenon as the subjective understanding of illness and that further study on the short version of the IPQ is necessary, especially with regard to the aspect of understanding the illness.…”
Section: Discussionmentioning
confidence: 99%
“…The result for MS and cancer patients in this research also proves that the understanding of illness may change in time. However, from the studies on the revised version of the questionnaire (IPQ-R) we conclude that in terms of illness coherence this stability refers to BC patients (Rees, Fry, Cull, & Sutton, 2004). The inconsistency suggests that one item cannot measure such a complex phenomenon as the subjective understanding of illness and that further study on the short version of the IPQ is necessary, especially with regard to the aspect of understanding the illness.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated increased anxiety in females with a family history of breast cancer [16,17]. Some studies have also shown that patients with a lower level of education report more breast-cancerspecific distress [18].…”
Section: Discussionmentioning
confidence: 99%
“…En cuanto a la representación que se tiene de esta enfermedad, históricamente se ha asociado con la muerte y la putrefacción, nociones que parecen perdurar también hasta la modernidad, lo que sugiere que las relaciones etimológicas establecidas en la historia, permiten indicar que el cáncer hace parte de un dispositivo de categorización que consume y devora el cuerpo 21 . Es claro entonces que la representación social del cáncer no solo está organizada alrededor del dolor y del sufrimiento (22,23) sino también de la muerte (12,24,25) , la mutilación, la incapacidad, el cambio a nivel social y familiar (25) , una enfermedad cruel que acarrea grandes pérdidas, asociada a sentimientos negativos como desesperación y miedo, y a quimioterapia (26) , que desestabiliza el proyecto de vida (5) , un flagelo social (12,24) y que estigmatiza (27)(28)(29) .…”
Section: Representaciones Sociales Del Cáncerunclassified